Empirical superior vena cava isolation in patients undergoing redo- catheter ablation procedure after recurrence of atrial fibrillation. (25th November 2020) - Spies, F; Madaffari, A; Voellmin, G; Krisai, P; Schaerli, N; Reichlin, T; Osswald, S; Sticherling, C; Kuhne, M; Knecht, S
Abstract: Background/Introduction: Extra pulmonary vein (PV) foci may trigger AF recurrence after an initially successful PVI. Superior vena cava (SVC) catheter ablation (CA) may therefore offer a treatment target in order to improve success rates. Purpose: The purpose of this study was to evaluate the potential benefit of empirical SVC isolation in addition to PVI in patients undergoing a second CA after index PVI. Methods: We retrospectively analyzed consecutive patients scheduled for a second CA because of a recurrence of symptomatic AF. Redo-CA was performed with a 3D electroanatomic mapping system and point-by-point ablation using RF energy in the range between 25 W and 30 W. In case of persistent isolation of all PVs, only SVCI was performed. In case of reconnection of vein(s), a wider antral re-isolation was performed. Redo-PVI (PVI-group) or Redo-PVI plus SVC isolation (SVCI) (PVIplusSVCI-group) were performed at the discretion of the operator. No additional targets were allowed. The endpoint of all procedures was elimination of the PV signals confirmed by a circular mapping catheter at the level of the PV ostium and elimination of all signals in the SVC in case of SVCI. Recurrence of AF during a follow-up of 12 months is presented. Results: We analyzed 191 patients (age 61±10 years, 30% female, BMI 27±5 kg/m 2, LVEF 56±9%, PLAX 41±7 mm, paroxysmal 61%). Whereas 148 (78%) patients underwent Redo-PVI only, 31 patients (16%) underwent PVI plus SVCI, and in 12 patients (6%) SVCI only was performed. Baseline characteristics did not differ significantly between the two groups. In the PVI-group, 79% were recurrence-free compared to 65% (see Kaplan-Meier curve: log rank p=0.011) in the PVIplusSVCI-group. The RF time of the PVI group focusing on the wide antral re-isolation of vein(s) was significantly higher than for the PVIplusSVCI-group (819±494 s versus 458±444 s; p<0.001). Conclusion: Additional empirical SVCI at redo-PVI in patients with symptomatic AF recurrence does not lead to an increase in freedom from AF recurrence. Focusing on an additional "wider antral" re-isolation may be more effective. Funding Acknowledgement: Type of funding source: None